EZH2 Expression in Intestinal Neuroendocrine Tumors. Issue 9 (October 2019) - Faviana, Pinuccia; Marconcini, Riccardo; Ricci, Sergio; Galli, Luca; Lippolis, Piero; Farci, Fabiola; Castagna, Maura; Boldrini, Laura
Abstract : Neuroendocrine tumors (NETs) arise from the cells present throughout the diffuse endocrine system. These neoplasms were previously regarded as rare, but in fact are increasing in incidence (3.65/100 000 individuals/y). Enhancer of zeste homolog 2 (EZH2) plays a crucial role in cell cycle regulation, and it was reported to be overexpressed in several tumors. The aim of the study was to investigate EZH2 expression, also related with proliferation rate, and p53 expression in NETs of the intestine encompassing a group of tumors primary to the stomach, appendix, small intestine, and colon. The specimens from 33 patients with neuroendrocrine tumors were investigated by immunohistochemistry for EZH2, p53, and Ki-67. Only 10 of 33 (30.3%) cases showed high EZH2 expression. High EZH2 levels significantly associated with elevated proliferation rates ( P =0.0012) and with elevated percentage of positive cells for p53 ( P =0.011). Our results suggest an association between p53 and the EZH2 pathway in NETs. EZH2 could represent a potential target antigen in cancer immunotherapy.